1995
DOI: 10.1099/13500872-141-10-2405
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, genetic analysis, and expression of Actinobacillus pleuropneumoniae transferrin receptor genes

Abstract: The tbpA and *pi? genes encoding the transferrin receptor proteins T b p l and Tbp2 from a serotype 7 strain of Actinobacillus pleuropneumoniae were cloned, sequenced, and expressed in Escherichia coli. The tbpB gene was preceded by putative promoter and regulatory sequences and was separated from the downstream tbpA gene by a 13 bp intercistronic sequence suggesting that the two genes may be coordinately transcribed. Determination of the nucleotide sequence of this region facilitated PCR amplification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
2
33
0
2
Order By: Relevance
“…In N. gonorrhoeae and N. meningitidis, two proteins (Tbpl and Tbp2) are responsible for binding transferrin to the cell surface [15]. Similarly, the genes for two transferrin binding proteins (Tbpl and Tbp2) have been cloned and sequenced in A. pleuropneumoniae [6]. In Neisseria species, the iron can be removed from transferrin or lactoferrin to the periplasmic space, and carried by Fbp to transport the iron molecule into the cells [15].…”
Section: Rbsa (N) 144mentioning
confidence: 99%
See 1 more Smart Citation
“…In N. gonorrhoeae and N. meningitidis, two proteins (Tbpl and Tbp2) are responsible for binding transferrin to the cell surface [15]. Similarly, the genes for two transferrin binding proteins (Tbpl and Tbp2) have been cloned and sequenced in A. pleuropneumoniae [6]. In Neisseria species, the iron can be removed from transferrin or lactoferrin to the periplasmic space, and carried by Fbp to transport the iron molecule into the cells [15].…”
Section: Rbsa (N) 144mentioning
confidence: 99%
“…pleuropneumoniae obtains iron from haem compounds [3] via the production hemolysins [4,5], and membrane-bound transferrin-specific receptors [6]. A. pleuropneumoniae probably binds the iron-loaded transferrin molecule to its surface and then, transports the iron from the transferrin into the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide primer sequences are based on the known sequences of the tbp operon in N. meningitidis B16B6 (27) and A. pleuropneumoniae H49 (17) and are listed in Table 1. PCRs were performed according to the manufacturer's instructions, and subsequent cloning steps undertaken with E. coli DH5␣ used standard molecular biology techniques (41).…”
Section: Methodsmentioning
confidence: 99%
“…The tbp operons from N. meningitidis, Neisseria gonorrhoeae, and Haemophilus influenzae (all specific to hTF), Actinobacillus pleuropneumoniae (specific to porcine TF [pTF]), and Pasteurella haemolytica (specific to bovine, sheep, and goat TFs) have been cloned and sequenced (1,17,18,27,33). Recombinant TbpA, recombinant TbpB, and truncated or chimeric TbpB proteins have been expressed and purified from Escherichia coli for binding studies (8,9,14,17,26,29,33,(36)(37)(38). However, the expression of heterologous or chimeric Tbp in members of the Neisseriaceae or Pasteurallaceae families, which would be useful for functional studies, has not been reported.…”
mentioning
confidence: 99%
“…The genes encoding TbpA and TbpB (tbpA and tbpB) are in an operonic arrangement, with tbpB preceding tbpA and putative regulatory and promoter sequences upstream of the tbpB gene (13,14,24). TbpB is a largely surface-exposed lipoprotein, capable of independently binding Tf and participating in the iron acquisition process, but it is not absolutely essential for iron acquisition in vitro (14).…”
mentioning
confidence: 99%